ANALISIS MANFAAT E- AGRICULTURAL MENGUNAKAN METODE SEMPLS (STUDY KASUS LIMAKILO.ID) - Andi Arfian (INTI Nusa Mandiri, 2020)
In the era of development of the world of digital information can be one of the answers to the challenges of the era in the current era. Answered, it answered the discussion in Indonesia, which was occasionally still haunted by the distribution chain that was too long and resulted in price spikes. One way is by implementing an online-based sales system and one of them is a partner with a profit sharing system between farmers and buyers. In its management, starting from capital lending, agricultural management, post-harvest processing to sales, packaging, to shipping. Each product supports the Limakilo.id website and the main objective is the empowerment of the Limakilo.id website for farmers in rural areas. In this study, researchers used the da Mclean delone model by using the sem method and qualitative pls tools. The purpose of this research is to study e-commerce. Most of the fields of agriculture can help improve the economics of farmers and villages in obtaining information on data but done through interviews, observations and direction of farmers and farmers of agricultural businesses in empowering the economy of rural communities in agriculture. The study analyzed activities regarding agricultural output in several villages in Sukamakmur District, Bogor Regency, West Java, using the system development model with the Delone and Mclean model and management data using SmartPls. From the results of this study it can be concluded that the limakilo e-commerce research. Id by Farmers also supports the agricultural economy in the villages is still very low in its utilization. Many are of the opinion and difficulties in carrying out these sales activities.